8. Identification of Parasites on the Shark Fish (Selachimorpha) in Peunayong Fish Market Banda Aceh City - Muttaqien Bakri; Iraidi Muharrir Asy’ari; Eliawardani Eliawardani; Muhammad Hambal; Winaruddin Winaruddin; Darmawi Darmawi; Azhari Azhari; Andi Novita (Jurnal Medika Veterinaria, 2020)
This study aims to identify ectoparasites and endoparasites in the Peunayong Fish Market, Banda Aceh City. The number of shark samples used in this study was 10 which were taken randomly. Parasitic examination is carried out on the surface of the body by means of scraping and natively. While examination of the visceral organs of fish by necropsy. Parasite identification was done by microscopic. The results showed that the Chilodonella sp. parasite infected the stingrays  of 10 sharks examined. The parasite species that infects sharks (Selachimorpha) in the Peunayong Fish Market in Banda Aceh City is Chilodonella sp, including the ectoparasite category that infects shark skin with a prevalence rate of 6.67%.